2004
DOI: 10.1111/j.1600-0722.2004.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Do different implant surfaces exposed in the oral cavity of humans show different biofilm compositions and activities?

Abstract: Osseointegrated dental implants play an important role in restorative dentistry. However, plaque accumulation may cause inflammatory reactions around the implants, sometimes leading to implant failure. In this in vivo study the influence of two physical hard coatings on bacterial adhesion was examined in comparison with a pure titanium surface. Thin glass sheets coated with titanium nitride (TiN), zirconium nitride (ZrN) or pure titanium were mounted on removable intraoral splints in two adults. After 60 h of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 45 publications
(57 reference statements)
6
79
0
2
Order By: Relevance
“…This strain was found in higher proportions on the a-C samples on both, rough and smooth surfaces, for both media MM or HS, suggesting that E. corrodens was more sensitive to surface chemistry than to roughness or the cultured media used. This finding supported the notion that chemical surface is directly affecting the colonization of the oral bacteria (Groessner-Schreiber et al, 2004). E. corrodens posses an specific lectin-like substance that mediates its adherence to various host tissue cell surfaces (Yamazaki et al, 1988), so it is possible that the specificity that this microorganism show to the a-C surfaces has to be with some specific adhesion properties of this strain.…”
Section: Prevotella Intermedia 25611supporting
confidence: 71%
See 1 more Smart Citation
“…This strain was found in higher proportions on the a-C samples on both, rough and smooth surfaces, for both media MM or HS, suggesting that E. corrodens was more sensitive to surface chemistry than to roughness or the cultured media used. This finding supported the notion that chemical surface is directly affecting the colonization of the oral bacteria (Groessner-Schreiber et al, 2004). E. corrodens posses an specific lectin-like substance that mediates its adherence to various host tissue cell surfaces (Yamazaki et al, 1988), so it is possible that the specificity that this microorganism show to the a-C surfaces has to be with some specific adhesion properties of this strain.…”
Section: Prevotella Intermedia 25611supporting
confidence: 71%
“…Studies about the peri-implant microbiota in vivo have examined the influence of oral health status on the presence of specific bacterial species. Some of these studies reported similar supra and subgingival microbiota on teeth and Ti implants (Shibli et al, 2008, Furst et al, 2007, Groessner-Schreiber et al, 2004. In contrast, other studies found an absence of periodontal pathogens like Aggregatibacter (formerly Actinobacillus) actinomycetemcomitans and Porphyromonas gingivalis (Heuer et al, 2007) or sporadic high numbers of Parvimonas micra (formerly Peptostreptococcus micros), Staphylococcus aureus and Staphylococcus epidermidis (Furst et al, 2007, Salvi et al, 2008.…”
Section: Introductionmentioning
confidence: 73%
“…Studies on nitride surfaces are sparse and the results are controversial. Some authors found unaltered or increased bacterial adhesion 41,112,123,124,150) on nitride titanium surfaces, but others found reduced biofilm formation [145][146][147][148][149]151,176) . Ji et al (2015) found TiN to show antimicrobial effects against S. mutans but not against P. gingivalis 177) .…”
Section: Nitride Surfacesmentioning
confidence: 99%
“…Two studies based on in vivo data confirmed the positive effect of TiN coating on the antibacterial activity of Ti surfaces. The results of Scarano et al [2] showed that implants coated with TiN illustrated a minor quantity of the surface covered by bacteria after a 24-h exposure to the oral cavity while a smaller bacterial quantity were found on TiN glass sheets compared to pure Ti coated glass sheets after 60 h of intraoral exposure [23]. TiN coatings seem to have a beneficial effect on antibacterial activity inhibiting the formation of microbial plaque, minimizing the adverse effects of peri-implantitis on implant longevity.…”
Section: Coatings In Implant Dentistrymentioning
confidence: 92%